Resources for the Assessment and Treatment of Substance Use Disorder in Adolescents - Emily Pender; Liana Kostak; Kelsey Sutton; Cody Naccarato; Angelina TsaI; Tammy Chung; Stacey Daughters (WikiJournal of Medicine, 2023)
Substance Use Disorder (SUD) is understood as the persistent use of substances to the detriment of the individual's livelihood and wellness. SUD can have serious mental, physical, and social ramifications if not properly addressed. Though SUD can develop at any age, it is especially important to address in adolescents, given rising prevalence of certain substances (e.g. cannabis) in that age group and poor prognosis associated with early-onset SUD. Data from the National Survey on Drug Use and Health show the lifetime use of illicit drugs in people ages 12-17 is 20.9%. The same survey found the rate of Substance Use Disorder in the past year for people ages 12-17 who used illicit drugs or alcohol to be 6.3% in 2020. This paper is intended for clinicians and lay people to gain a deeper understanding of SUD in adolescents, particularly relating to alcohol, cannabis, nicotine, and opioids. Though alcohol, cannabis, and nicotine are the substances most commonly used by this age demographic nationally, opioid use – and resulting deaths – have been on the rise. According to the Centers for Disease Control and Prevention (CDC), opioids were connected to about 75% of the nearly 92,000 drug deaths in 2020. Beyond significant death rates in the general population, recent spikes in adolescent death rate tied to the synthetic opioid fentanyl – which held a relatively stable death rate from 2010 to 2019 until seeing a 94% increase from 2019 to 2020 and additional 20% increase to 2021 - warrants inquiry into opioids for this population. Each of these substances can have adverse, long-lasting effects on health if not managed properly, resulting in seriously compromised lifelong wellbeing. This article explores SUD prevalence and reviews diagnostic criteria in relation to adolescence, including a synopsis of changes in SUD classification between the DSM-IV and DSM-5 and discussion of ICD-11 and the Research Domain Criteria (RDoC) as a basis for research related to substance use. Effective assessment and consideration of co-occurring disorders are covered as well. Although the prognosis of SUD varies by an individual's environment and circumstances, a modal developmental course for SUD is discussed. Finally, a curated list of nationally recognized resources including hotlines, treatment locators, informational sites, and support groups is provided, along with tools to compile local resources. By addressing these aspects of adolescent SUD, the research team offers a broader view of its prevalence in the United States, key warning signs and comorbidities, and possible assessments and treatments for adolescents with SUD.